1991
DOI: 10.1093/carcin/12.3.503
|View full text |Cite
|
Sign up to set email alerts
|

DNA adducts in lymphocytes and granulocytes of smokers and nonsmokers detected by the 32P-postlalbelling assay

Abstract: The effects of smoking and DNA adduct formation were analysed in isolated human white blood cell populations. As the white cells are composed mainly of granulocytes with a short half-life and T-lymphocytes with a half-life of several years, we isolated the lymphocytes and granulocytes of 11 smokers and 10 nonsmokers to determine any smoking-related DNA adducts by the nuclease-P1-enhanced 32P-postlabelling assay. The differences between the mean lymphocyte DNA adducts/10(8) nucleotides of 31 +/- 5.7 (SE) of smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(51 citation statements)
references
References 0 publications
6
45
0
Order By: Relevance
“…Direct correlations among surrogate tissue and target tissues, however, are few in number. An early important observation was that smoking effects on adducts were stronger when measurements were made using DNA isolated from blood MNC compared with the DNA from the short-lived granulocyte fraction of WBC (Savela and Hemminki, 1991). In a subsequent study, hydrophobic-DNA adducts in blood MNCs were found to be a reliable surrogate of lung DNA adduct levels (Wiencke et al, 1995).…”
Section: Dna-adducts and Exposure To Lung Carcinogensmentioning
confidence: 99%
“…Direct correlations among surrogate tissue and target tissues, however, are few in number. An early important observation was that smoking effects on adducts were stronger when measurements were made using DNA isolated from blood MNC compared with the DNA from the short-lived granulocyte fraction of WBC (Savela and Hemminki, 1991). In a subsequent study, hydrophobic-DNA adducts in blood MNCs were found to be a reliable surrogate of lung DNA adduct levels (Wiencke et al, 1995).…”
Section: Dna-adducts and Exposure To Lung Carcinogensmentioning
confidence: 99%
“…The 32P-postlabeling technique for estimating aromatic adducts to DNA has been employed for potroom workers, peripheral white blood cells being used as the surrogate tissue (16)(17)(18)(19). Total counts of white blood cells are not optimal, however, for adduct studies due to the predominance of short-lived granulocytes (20). It is more relevant to assess the effect of long-term exposure to PAH in peripheral lymphocytes which have a longer mean half-time.…”
mentioning
confidence: 99%
“…Approximately 70% of total white blood cells are short-lived granulocytes, whereas the remaining 30% are longer-lived MNCs.3 Total white blood cell aro matic DNA adduct levels were found to be associated neither with active cigarette smoking (14,16,26) nor with adduct levels measured in lung tissue from the same individuals (27). In other studies, how ever, aromatic DNA adduct levels from MNCs were found to be increased in current smokers (28) and were reproducibly measured by the 32P-postlabeling assay over time (29). Consequently, we propose that long-lived MNCs should be a valid surrogate tissue for assessing chronic exposure to tobacco carcinogens.…”
Section: Introductionmentioning
confidence: 93%